When education becomes business - Abd Razak, Dzulkifli (2005)
IN our search for educational excellence, the possibility of bogus universities offering degrees in Malaysia, as reported recently, has come as a surprise to many people. And that there were Malaysians who graduated from these "universities" is even a bigger shock. More so now that the outgoing Irish ambassador has confirmed that the "universities" had no ties with Ireland. Reportedly, he had forwarded the case to the Irish authorities to take action against the people behind the scam. Similarly, the Malaysian authorities are also doing the same. Earlier, the issue of agents recruiting local students for foreign universities was highlighted. Allegedly this is one source of problem leading to students being enrolled in unrecognised universities overseas. Thus, by the same token, the hiring of agents by local universities to recruit foreign students can also be problematic as most see this as no more than an economic venture.